Mind in eBay, body in Macy's: Dual consciousness of virtuo-physical consumers and implications for marketers. Issue 4 (10th October 2016) - Banerjee, Syagnik; Longstreet, Phil
Abstract : Purpose: With the ubiquitous diffusion of mobile-enabled internet, individuals are constantly immersed in both virtual and physical environments. While this causes distractions, lower attention spans and disasters such as texting while driving and walking, it also creates synergies and smoother navigational experiences. Technology developers, marketers and policy-makers are both concerned and intrigued to understand how to deploy these mobile technologies so as to optimize their disruptive impact. In this paper, the authors aim to develop a framework of dual consciousness to understand the potential causes and outcomes of individual's simultaneous presence in physical and virtual worlds. Design/methodology/approach: A careful review of past academic literature on behavior, as well as media reports of incidents of disruptions, led the authors to construct a 2 × 2 framework depicting behaviors that indicated high-low consciousness in physical, as well as virtual worlds. Findings: In dual environments, individuals either dissociate from one of the environments or integrate both environments. While the former is driven by the multiplicity of irrelevant roles and goals, oblivion of relevant roles, perception of group norms and performance of practiced routine tasks, the latter is driven by strong executive control processes, focused singular goals and usage of the virtual environment to reinforce their physical tasks. The most affected parties are retailers, service providers, digital marketers and social media marketers. Originality/value: Most prior research in interactive marketing examine effects of online stimuli on online behavior. This paper identifies the noise created by physical context on clicks as well as the interference created by virtual stimuli on physical purchases and service experiences.